2008
DOI: 10.1016/j.drugalcdep.2007.07.012
|View full text |Cite
|
Sign up to set email alerts
|

The association of self-reported neighborhood disorganization and social capital with adolescent alcohol and drug use, dependence, and access to treatment

Abstract: Aims-This research examines adolescent perceptions of neighborhood disorganization and social capital to determine if they are associated with adolescent alcohol or drug (AOD) use, AOD dependence, and access to AOD treatment.Design-This is a secondary analysis of data from the 1999 and 2000 National Survey on Drug Use and Health (NSDUH). The NSDUH is a cross-sectional survey of a random sample of the noninstitutionalized United States population and is conducted in respondents' homes.Participants-Youth between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
4
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 42 publications
(40 reference statements)
6
102
4
3
Order By: Relevance
“…Other neighborhood trajectories, namely radically improving and slightly improving, did not predict marijuana use in the sample. These fi ndings are consistent with cross-sectional studies that demonstrate a relationship between neighborhood disadvantage and adolescent drug use and exposure (Crum et al, 1996;Fite et al, 2009;Winstanley et al, 2008). Crum et al (1996) found that adolescents living in the most disadvantaged neighborhoods were more likely to have been offered cocaine than adolescents living in more advantaged communities (OR = 5.6, p = .001).…”
Section: Discussionsupporting
confidence: 79%
“…Other neighborhood trajectories, namely radically improving and slightly improving, did not predict marijuana use in the sample. These fi ndings are consistent with cross-sectional studies that demonstrate a relationship between neighborhood disadvantage and adolescent drug use and exposure (Crum et al, 1996;Fite et al, 2009;Winstanley et al, 2008). Crum et al (1996) found that adolescents living in the most disadvantaged neighborhoods were more likely to have been offered cocaine than adolescents living in more advantaged communities (OR = 5.6, p = .001).…”
Section: Discussionsupporting
confidence: 79%
“…Youth who live in more disadvantaged neighborhoods are more likely to report psychological distress and substance use during adolescence than youth living in areas with fewer disadvantages. [33][34][35] This is particularly troublesome for HIV prevention given the robust relationship between condom use and psychological distress and substance use. [36][37][38] Economic disadvantage may also influence the composition of sexual networks and place youth at risk for greater HIV/STI vulnerability.…”
Section: Social Disorganization Theory: a Conceptual Framework To Examentioning
confidence: 99%
“…For example, proximity of alcohol outlets and outlet density have been related to youth drinking and drinking problems (e.g., Chen et al, 2010;Huckle et al, 2008;Treno et al, 2003;Truong and Sturm, 2009) and to the likelihood of using social and commercial sources of alcohol (Paschall et al, 2007). Likewise, neighborhood characteristics-such as residential instability, percentage in poverty, and overall disadvantage-have been found to be related to increased adolescent drug and alcohol use (Buu et al, 2009;Duncan et al, 2002;Winstanley et al, 2008).…”
Section: Rinking By Young People Is Associatedmentioning
confidence: 99%